Solubility and saturation apparent specific volume of some sodium sulfonamides in propylene glycol + water mixtures at 298.15 K (2015)
Equilibrium solubility of sodium sulfadiazine (Na.SDZ), sodium sulfamerazine (Na.SMR), and sodium sulfamethazine (Na.SMT), was determined in aqueous binary mixtures of propylene glycol (PG) at 298.15 K. If the solubility values expressed in both concentration scales are considered, i.e. mole fraction and molarity, in water-rich mixtures the solubility decrease as: Na.SDZ > Na.SMT > Na.SMR, whereas, in PG-rich mixtures the observed order is: Na.SMT > Na.SDZ > Na.SMR. In all cases the solubility in neat water is higher than those in neat PG. Correlation of the solubility data obtained was made by means of the Jouyban-Acree model for all the sodium sulfonamides. Otherwise, apparent specific volumes (FVsp) of sodium sulfonamides at saturation were also calculated in all the mixtures. The average FVsp values are as follows: 0.663 cm3 g- 1 for Na.SDZ, 0.723 cm3 g- 1 for Na.SMR, and 0.740 cm3 g- 1 for Na.SMT, with a variation lower than 5.0% in each case. © 2015 Elsevier B.V. All rights reserved.